The European Union in the Asia-Pacific rethinking Europe's strategies and policies - Song, Weiqing, 1969-; Wang, Jianwei (Manchester University Press, 2019)
Since the mid-1990s, the European Union has defined the Asia Pacific as one of its key strategic targets on its ambitious road towards a global power. Over the past decades, big changes have taken place on both sides and the wider world. It's high time to evaluate the EU's performance in its Asian policy. In fact, the EU is at crossroads with its Asia Pacific policy. On several aspects, the EU is compelled to redefine its interests and roles, and rethink its strategies and policies towards the dynamic and ever important Asia Pacific region. This volume addresses this theme, by elaborating the general context, major issues and countries in the EU's Asia Pacific policy. It covers issue areas of traditional security, economy and trade, public diplomacy, and human security and focuses on the EU's relations with China, Japan, the ASEAN countries, and Australasia